City Charter of the City of Hastings 74 (1870) - (:unkn) unknown (My University, 1870)
Ordinance No. 74-An Ordinance Relating to Breaches of the Peace, Disorderly Conduct and the Carrying of Concealed Weapons, § 3: Any person who shall go armed within the incorporated limits of said city of Hastings with a dirk, dagger, sword, pistol or pistols, or shall carry a slung-shot or metal knuckles or other offensive or dangerous weapon, without reasonable cause to fear an assault or other injury to his person or to his family or property, shall, upon conviction before said justice, be punished by a fine not exceeding one hundred dollars, or by imprisonment not exceeding three months, or both, in the discretion of the justice."
Keywords: CARRY